2006
DOI: 10.1002/mnfr.200500216
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐human immunodeficiency virus activity of 3,4,5‐tricaffeoylquinic acid in cultured cells of lettuce leaves

Abstract: 3,4,5-Tricaffeoylquinic acid (TCQA) that is not found in intact plant of lettuce leaves was isolated from the cultured cells. The intact plant produced chicoric acid (dicaffeoyl tartaric acid: L-CCA) as well as chlorogenic acid (3-caffeoylquinic acid: 3-CQA) as the major metabolites. After subculturing of the cells for 40 days, the amount of 3,4,5-TCQA reached to 0.14 mg/g fresh weight. The inhibitory effect of 3,4,5-TCQA for human immunodeficiency virus (HIV) Type 1 integrase was assayed. Anti-HIV activity us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…In a callus culture of L. sativa var. crispa L. (Tamura et al 2006) 3,5-DCQA predominated (leaves of the parent plant contained 3.8 times less of 3,5-DCQA than the cultured cells). Similar change in hydroxycinnamate accumulation pattern (domination of 3,5-DCQA) was observed in our callus and root cultures (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In a callus culture of L. sativa var. crispa L. (Tamura et al 2006) 3,5-DCQA predominated (leaves of the parent plant contained 3.8 times less of 3,5-DCQA than the cultured cells). Similar change in hydroxycinnamate accumulation pattern (domination of 3,5-DCQA) was observed in our callus and root cultures (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Because of their beneficial effects on health (Navarre, 2009;Monro and Mishra, 2009) they are as important as phenolics, flavonoids, folate, anthocyanins, poly-amines and carotenoids (Ezequiel et al, 2013), which are considered as antioxidants, protecting against reactive oxygen species (ROS) when consumed through diet (Virgili and Scacini, 2003;Kris-Etherton et al, 2004). The bioavailability of these metabolites in potatoes seems to have benefits for human health, in anti-hypertensive activity, prevention of atherosclerosis, type 2 diabetes, Alzheimer's disease, cancer (Zhao and Moghadasian, 2010); there is also evidence of their inhibitory effect against HIV (Tamura et al, 2006), cataracts and macular degeneration (Chuah et al, 2008) and of antimicrobial properties (Muthuswamy and Ruspasinghe, 2007). As a therapeutic alternative, potatoes are also used empirically by the population for problems of the gastric mucosa, which shows that fresh potatoes and tocosh (an andean preservation technique) have an antioxidant defense and cytoprotective effect on the gastric mucosa (Sandoval-Vegas et al, 2010;Sandoval et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also found that the amount of 3,5-diCQA in cultured cells reached 0.83 mg/g fresh weight, which was 3.8-fold higher than its amount in intact plants 17 . Establishment of techniques to obtain caffeic acid derivatives in large quantities from cultured cells is therefore expected to gain importance.…”
Section: Resultsmentioning
confidence: 92%
“…Recently, Tamura et al reported that 3,4,5-triCQA, which was not found in intact lettuce leaves, was produced in cultured cells derived from plant materials, and the 3,4,5-triCQA amount reached 0.14 mg/g fresh weight 17 . The authors also found that the amount of 3,5-diCQA in cultured cells reached 0.83 mg/g fresh weight, which was 3.8-fold higher than its amount in intact plants 17 .…”
Section: Resultsmentioning
confidence: 99%